The Potential of Mango (Mangifera infica L.) Peel of Apple Varieties By Infusion And Maceration In Inhibiting Pseudomonas aeruginosa And Propionibacterium acnes: Potensi Kulit Mangga (Mangifera infica L.) Varietas Apel Secara Infusa Dan Maserasi Dalam Menghambat Bakteri Pseudomonas aeruginosa dan Propionibacterium acnes - Rahmawati, Vifin Putri; Rini, Chylen Setiyo (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Plants have many chemical components. The use of natural ingredients as an alternative treatment in dealing with diseases, especially acne. One of them is mango (Mangifera indica L.) varieties of apples obtained at the Larangan Main Market in Sidoarjo. This study aims to determine the potential of infusion and maceration of mango skin varieties in inhibiting Pseudomonas aeruginosa and Propionibactrium acne at various concentrations. This antibacterial potential test was carried out using the diffusion method of the wells. The antibacterial potential is characterized by the formation of a clear zone around the well called the inhibition zone. This study uses 10 concentrations namely 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% and Clindamycin as positive control and aquades as negative control. Based on the results of the Two Way ANOVA test data obtained were not normally distributed, therefore a comparison test was performed using the Kruskal-Wallis test with a sign value (α <0.05). This showed that there were significant differences in the use of various concentrations. The maceration extract concentration of 100% is the best concentration to form a zone of inhibition against P. aeruginosa of 17.9 mm and P. acne bacteria of 13.2 mm. The results of the infusion extract concentration did not form inhibitory zones in both of P. aeruginosa and P. acnes.